The language of leadership in Laos. (April 2017) - Case, Peter; Connell, John G.; Jones, Michael J.
This paper responds to recent calls in the leadership studies literature for anthropologically informed empirical research on leadership phenomena in non-Western and non-Anglophone settings. The authors have worked extensively on rural development projects in Laos and draw on ethnographic 'observant-participation' and interview data to explore how leadership is construed in a contested terrain where traditional concepts intersect with those of official government and international development agencies. A theoretical discussion of linguistic relativity and the socially constitutive nature of language in general is offered as background justification for studying the language of leadership in context. The anthropological distinction between etic and emic operations is also introduced to differentiate between various interpretative positions that can be taken in relation to the fieldwork and data discussed in this paper. The study shows how difficult it can be for native Lao speakers to find words to describe leadership or give designations to 'leaders' outside of officially sanctioned semantic and social fields. A key finding of the study is that, viewed from the perspective of the Lao People's Revolutionary Party, authority and leadership are coextensive . This social fact is reflected in the linguistic restrictions on what can and cannot be described as leadership in Laos.